A Proustian Reading of Michel Onfray's Cosmos and Christian Signol's Les vrais bonheurs: "Privileged Moments" of Sensorial Ecstasy - Moser, Keith (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2021)
This study probes the philosophical significance of the strange joy induced by a trigger sensation that immediately strikes the reader in Michel Onfray’s Cosmos and Christian Signol’s Les vrais bonheurs. Heavily influenced by Proust’s vision of involuntary memory, the role of the senses, and the nature of time in A la recherche du temps perdu, Onfray and Signol attempt to explore the essence of everything in the context of powerful, transformative sensorial encounters. Some critics automatically dismiss the rending ecstasy depicted by the Proustian narrator in the “petite madeleine” scene as nothing more than a form of whimsical artistry. However, Onfray and Signol’s rewriting of this renowned passage demonstrates that the notion of a privileged moment, associated with Proust in French literary circles, is an all-encompassing metaphor for delving into the most fundamental philosophical questions of all.